Pelaksanaan Anggaran Pendapatan Dan Belanja Sekolah Berbasis Total Quality Management (TQM) - Nasution, Mimin Sundari (Jurnal Ilmu Administrasi Negara (JUAN), 2016)
The education system is expressed as a civilizing process learners that lasts a lifetime. Educational institutions are not able to manage the change, will be missed. Because this is in line with the paradigm shift in the organization of the market oriented to resources oriented, then that could be taken is to reorganize its resources in order to survive in the long-term competitiveness. One appropriate way is to implement Total Quality Management. Providing education and finance contained in budgets (Budget School) is integral. The essence of interest budgets, presumably not a matter of profit and loss, but how the educational needs in schools can be fulfilled. This paper will discuss the implementation of TQM-based budgets with a view across the indicators are customer focus, continuous improvement, management comitment to quality, and employee empowerment